Transforming Islamic Education Curriculum in the Era of Religious Moderation: Between Digital Integration and the Resilience of Pesantren Values - Munawar, Muhamad Aris; Endang, Ujang (Bestari, 2025)
This article examines the ongoing transformation of Islamic education curriculum in Indonesia as the country promotes the national agenda of religious moderation. The study explores how Islamic schools and universities negotiate the tension between digital integration—accelerated by the expansion of online learning—and the preservation of pesantren values that emphasize character formation, spiritual discipline, and traditional scholarship. Using a qualitative approach, data are drawn from curriculum documents, interviews with educators, and observations of instructional practices in selected institutions. Findings reveal that digital learning environments have broadened access to Islamic knowledge but simultaneously challenge the depth of interpersonal transmission central to pesantren pedagogy. The curriculum reforms highlight a hybrid model that seeks to balance technological innovation with ethical, cultural, and theological continuity. The paper argues that successful integration depends on strengthening teachers’ digital pedagogical competence while ensuring that core religious values remain integral to instructional design. This study contributes to understanding how Muslim-majority countries can harmonize modernization and tradition within Islamic education systems.